Metodologia da problematização na educação física escolar: estratégias didáticas e princípios metodológicos - Liziero, Leonardo; Romero, Luiz Rogério [UNESP] (Caderno de Educacao Fisica e Esporte, 2025)
BACKGROUND: The Problematization Methodology with the Maguerez Arc (PMMA) is a methodological path with growing interest in physical education (PE) at school, especially due to the possibility of contextualizing social reality with the theme studied.OBJECTIVE: The present study aimed to identify teaching strategies and methodological principles of PMMA in PE.METHODS: A participative research was carried out with pedagogical intervention of 13 classes with 3 groups of 5th grade of Elementary School. The data were collected in a field diary and a reflective thematic analysis was carried out. For this study, the analyses were centered on the following themes: (1) planning strategies and (2) challenges, adaptations and reflections on the PMMA stage.RESULTS: Didactic strategies and methodological principles were identified in the application of PMMA in PE, organized in guiding frameworks. PMMA enabled the systematization of a pedagogical work that addresses different dimensions of knowledge and is directed towards the social reality of the students. On the other hand, the culmination of the students' work was centered on the body experiments carried out.CONCLUSION: PMMA was presented as a methodological possibility for PE and possibilities of teaching strategies were systematized for each stage of the arc. It is suggested that studies be expanded to include other themes and knowledge, as well as in other stages of basic education.